Performance and Energy Efficiency Analysis of Nanofluid-based Engine Cooling System - Zulfan, Zulfan (SEAN Institute, 2024)
This investigation is intended to examine the performance and energy-efficient characteristics of nanofluid-based engine cooling systems. A qualitative method was employed with a case study approach to investigate the application of nanofluids in industrial engine cooling systems. The data set was constructed through the use of in-depth interviews, direct observation, and the analysis of relevant technical documentation. The resulting findings indicated that the implementation of nanofluids has the potential to enhance the heat transfer capacity and energy efficiency of the cooling system, with improvements observed in comparison to the performance of conventional fluids. The effectiveness of the system is influenced by a number of factors, including the concentration of nanoparticles, the specific nanomaterial utilized, and the operational parameters. The insights gained from this investigation offer significant value for the advancement of nanofluid-based refrigeration technology